ANALYSIS OF MACRO AND MICRO ELEMENTS AND WATER-SOLUBLE VITAMINS OF THE PLANT CYNARA SCOLYMUS L. (Scientific journal of the Fergana State University, 2024)
The content of macro and micro elements and vitamins in plants is considered one of the important factors that determine their beneficial properties. Humans satisfy the need for macro and micro elements necessary for the body during their life activities, as well as vitamins, mainly by consuming plant products. Naturally in this case it is very important to know which plants store these products in large quantities in their composition. We also analyzed the macro-and micro-element and vitamin composition of the Cynara scolymus L. plant, which is appreciated for a number of its beneficial properties during our study. Studied the composition of water - soluble vitamins, macro-and microelements in the plasma Cynara scolymus L. plant with high-performance liquid chromatography and inductively coupled mass spectrometry, Grows in different regions of the Republic of Uzbekistan. It was found that the amounts of vitamins, macro and microelements in different vegetative parts of Artichoke differ among themselves.